2014
DOI: 10.1007/s10792-014-9969-x
|View full text |Cite
|
Sign up to set email alerts
|

The role and treatment of inflammation in dry eye disease

Abstract: Dry eye syndrome is a common ocular surface problem, affects 10-30 % of the population, especially in those who are older than 40 years. As a consequence of the demographic pressure created by the aging population, its prevalence is expected to increase as well as its burden on ophthalmologic practices. Thus, understanding the complex underlying mechanisms and development of thoughtful, effective strategies that involve these mechanisms are critical. Many factors causing ocular surface damage and inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 95 publications
(90 reference statements)
2
48
0
1
Order By: Relevance
“…[149] Overall, Tregs are naturally tuned to regulate the proliferation of pathogenic effector T cells, and maintain immunological homeostasis in the ocular tissue. [151] …”
Section: Ocular Diseasesmentioning
confidence: 99%
“…[149] Overall, Tregs are naturally tuned to regulate the proliferation of pathogenic effector T cells, and maintain immunological homeostasis in the ocular tissue. [151] …”
Section: Ocular Diseasesmentioning
confidence: 99%
“…Complications of corticosteroid eye drops should be taken into consideration since dry eye is a chronic problem. Therefore, they should be used as an acute phase treatment option in patients who are not relieved by other treatments [42]. The first topical cyclosporine eye drop, RestasisTM 0.05%, received FDA approval in 2002 for the treatment of inflammation in dry eye syndrome.…”
Section: External Eye Diseasesmentioning
confidence: 99%
“…They also decrease lipase activity, regulate meibomian lipids, and decrease MMP-8 levels [49]. Oral tetracycline can be used 250 mg 4 times daily, or as doxycycline or minocycline 100 mg once or twice daily [42]. Autologous serum is rich in epitheliotropic factors, neurotrophin, vitamin A, immunoglobulin, and extracellular matrix proteins.…”
Section: External Eye Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of cancers are associated with inflammatory responses (Arthur et al, 2012;Bishayee, 2014;Elinav et al, 2013;Gomes et al, 2014;Sfanos et al, 2014), the preventive characteristics of vitamin D have been tested in cancers and it has been shown that vitamin D deficiency is a risk factor (Krishnan & Feldman, 2011). Similarly, inflammation component appears to play a key role in the etiopathogenesis of ocular surface dryness (Wei & Asbell, 2014;Yagci & Gurdal, 2014). Galor and colleagues (2014) surveyed 247 elder males and investigated the effects of diet and vitamin D levels on dry eye.…”
Section: Dry Eye Diseasementioning
confidence: 99%